1996
DOI: 10.1002/j.2050-0416.1996.tb00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Activity of Sorghum Lipase During Malting and Mashing

Abstract: Lipase activity was monitored during malting and mashing of sorghum grains. All three sorghum varieties contained detectable lipase activity in the ungerminated form. Lipase activity changed only slightly during steeping for 24 hours but increased several fold in the course of germination. Between 24% and 60% of the lipase activity of the green malt was retained after kilning at 48°C but no activity was detected in the wort after mashing at 65°C. About 68% of the lipase activity of 72 hours old malt was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Nwanguma et al (1996) detected lipolytic activity in non-germinated sorghum seeds during grain malting and mashing. The authors observed a slight decrease in enzyme activity during steeping for 24 hours, but IT increased several fold in the course of germination.…”
Section: Sorghum Lipase (Sorghum Bicolor L)mentioning
confidence: 95%
“…Nwanguma et al (1996) detected lipolytic activity in non-germinated sorghum seeds during grain malting and mashing. The authors observed a slight decrease in enzyme activity during steeping for 24 hours, but IT increased several fold in the course of germination.…”
Section: Sorghum Lipase (Sorghum Bicolor L)mentioning
confidence: 95%
“…Lipase activity was assayed using a modified method of Vyas and Patel [31] as reported by Nwanguma et al [20]. A half gram (0.5 g) of the crude enzyme was added to a reaction mixture prepared by mixing 1 ml of corn oil and 3 ml of 0.1 M phosphate buffer, pH 8.0, in 25-ml flasks.…”
Section: Assay For Lipase Activitymentioning
confidence: 99%
“…In the malts, a-and b-amylase activities were determined by the diamylase procedure of EtokAkpan and Palmer 16 , diastatic activity by the method of Hulse et al 29 , while lipase activity was monitored by a modification of the method of Nwanguma et al 42 . The modifications consisted of using 18 mL of 0.1M phosphate buffer instead of 3 mL; during fermentation, 4.5 mL of the fermenting liquor was used in place of 0.5 g of the acetone powder.…”
Section: (Ixivqmrexmsr Sj Ir^]qi Egxmzmxmiwmentioning
confidence: 99%
“…The fatty acids released during TAG hydrolysis are linear with increasing concentration of enzyme 46 and are used in the provision of metabolic energy, in glucose synthesis 31 when aleurone and scutellar soluble sugars are depleted or as precursors for synthesis of phospholipid necessary for the proliferation of cellular endomembrane systems 56,61 . Lipase activity increases during malting of sorghum grains 42 and germination of oleaginous seeds 46 . In sorghum seedlings, about 68% of the lipase is found in the plumule, 29% in the endosperm, and 3 percent in the radicle.…”
mentioning
confidence: 99%
See 1 more Smart Citation